Evaluation of the uric acid and hematological parameters in patients with nodal hand osteoarthritis - Ünal Enginar, Ayşe (The European Research Journal, 2023)
Objectives: To compare patients with symptomatic nodal hand osteoarthritis (OA) with a control group in respect of inflammation parameters, uric acid, and hematological parameters. Methods: The study included 50 post-menopausal female patients, aged 40-80 years, diagnosed with symptomatic nodal hand OA, and a control group of 50 post-menopausal females in the same age range with no hand OA. Patient data including age, monocyte, neutrophil, lymphocyte, and thrombocyte counts, erythrocyte sedimentation rate (ESR), C-reactive protein (CRP) level, uric acid level, and the Kellgren-Lawrence (KL) score obtained from evaluations of hand radiographs, were recorded retrospectively from the hospital information system. The neutrophil-lymphocyte ratio (NLR), platelet-lymphocyte ratio (PLR), and monocyte-lymphocyte ratio (MLR) were calculated. The data were compared between the two groups. Results: The data of 100 females were compared, comprising a patient group of 50 patients with symptomatic nodal OA, and a control group of 50 females. Age, monocyte, neutrophil, lymphocyte, and thrombocyte counts, NLR, PLR, MLR, ESR, CRP, and uric acid level were compared. With the exception of MLR and ESR, no statistically significant difference was determined between the two groups. The MLR was determined to be statistically significantly higher in the control group than in the patient group (p = 0.024). The ESR was determined to be statistically significantly higher in the patient group than in the control group p < 0.001). When patients with a KL score of 2 and 3 were compared, with the exception of age, no other difference was determined. Patients with a KL score of 3 were seen to be significantly older (p = 0.032). Conclusions: ESR was determined to be significantly higher in patients with symptomatic nodal OA. Clarification of the relationship between inflammation, uric acid, and hand OA, which is a heterogeneous disease, will be useful in the follow-up and treatment of patients.